Fundamentals of Statistics with Fuzzy Data - Nguyen, Hung T.; Wu, Berlin (Studies in Fuzziness and Soft Computing, 2006)
This research monograph presents basic foundational aspects for a theory of statistics with fuzzy data, together with a set of practical applications. Fuzzy data are modeled as observations from random fuzzy sets. Theories of fuzzy logic and of random closed sets are used as basic ingredients in building statistical concepts and procedures in the context of imprecise data, including coarse data analysis. The monograph also aims at motivating statisticians to look at fuzzy statistics to enlarge the domain of applicability of statistics in general. HUNG T. NGUYEN is a professor of Mathematical Sciences at New Mexico State University, USA. BERLIN WU is a professor of Mathematical Sciences at National Chengchi University, Taipei, Taiwan.